Changing the Personal Hygiene Behavior of Preschool by Reading Stories from Contemporary Books - Yuni Sufyanti Arief; Ifa Maftukhatin Farokha; Ni Ketut Alit Armini (Jurnal Ners, 2010)
Introduction: Personal hygiene is an action to maintain a hygiene and body health. This condition must be caring by everyone, because various of desease can happen in lack consequence of hygiene. This study was aimed to investigate the effect of health education with contemporary book story on preschool personal hygiene behaviour (knowledge, attitude, action) at RA Perwanida, Mojokerto.Methods: Design use in this study was Quasy Experimental design. The population had taken from RA Perwanida, Mojokerto, in July 2009, whom deal directly with the preschool parents. Total sample was 22 respondents who met B class in RA Perwanida, Mojokerto. They were divided into 2 groups, treatment and control groups. Data were collected by using questionnaire and observation sheet. Data were analyzed by using Wilcoxon Signed Rank Test with significance level of α ≤ 0.05 and Mann Whitney U Test with signi fi cance level ofα ≤ 0.05.Result: Results revealed the presence of effect in treatment and control groups. In treatment group the level of dependence due to preschool knowledge had signi fi cance level of p = 0.002, while that in control group was p = 1.000, to preschool attitude p = 0.034 in treatment, and p = 0.014 in control group, to preschool action p=0.001, and p = 0.317 in control group.Conclusion: It can be concluded that there are significant influence of health education with contemporary book story on preschool personal hygiene behaviour. Further study should measure qualitation of understanding about personal hygiene behaviour for teacher in RA Perwanida, Mojokerto.